Odpowiedzi

2010-03-17T16:25:53+01:00
A) 3(x+2)+2(2x-3)=-12+3
3x+3+4x-6=-12+3
3x+4x=-12+3-3+6
7x=-6 /:7
x=-6/7 (minus sześć siódmych)

b) 1-x-3 kreska ułamkowa : 2 =2x /*2
1-x-3=4x
1-3=4x+x
-2=5x /:5
x=-2/5

c) 2-x-3 kreska ułamkowa : 3 =x /*3
2-x-3=3x
2-3=3x+x
-1=4x /:4
x=-1/4



2010-03-17T16:26:44+01:00
A) 3x+ 6 + 4x - 6=12+3
3x+4x=12+3-6+6
7x= 15 | :7
x=2,14

b) 1-x-3
_____ = -12+3 | *2
2
2-2x-6 = -24 + 6
-2x= -2 +6 +6-24
-2x= -14 | : -2
x=7

c) 2-x-3
_____ = x | *3
3

6-3x-9 = 3x
6-9=3x+3x
-3=6x | :6
x= -0,5
2010-03-17T17:16:16+01:00
3(x+2)+2(2x-3)=-12+3
3x+6+4x-6=-12+3
7x=-12+3-6+6
7x=-9 /7
x= -1 2/7

1- x-3 kreska ułamkowa : 2 =2x

1- (x-3/2)=2x *2
2-x+3=4x
-5x=-5 /-5
x=1


2- x-3 kreska ułamkowa : 3 =x

2-(x-3/3)=x /*3
6-x+3=3x
-4x=-9 /-4
x= 2 1/4